Types of the 3rd Prophet's Herbal: Honey Bees (Salwa) - Amiruddin, Muhammad; Salsabila, Agisha Salwa; Wibawati, Diva Aulia Putri; Mulpiawan, Nadiya Ramadanty; Sari, Yulia Anita (Proceeding Annual Symposium on Hajj and Umrah Medicine, 2022)
Health is a hope for every human being. In Islam, maintaining health (hifdzun nafs) is one of the fundamental parts of the main maintenance principles of the Shari'a (maqâsidusy syarî'ah). Islam commands His people always to maintain their health and seek treatment when they are attacked by illness. Honey and vinegar are examples of Thibbun Nabawi at the time of Rasulullah SAW., which has many benefits, especially for health and medicine. This research aims to learn more about the existence of bee honey (Salwa) and vinegar in the Al-Qur'an and Hadith, their contents and benefits, and how to process them for health. The research method used is in the form literature review by surveying journal literature that is relevant to the topic. The results of this study indicate that honey and vinegar have various therapeutic properties. Honey can be used as an antimicrobial, wound healer, antifungal, antidiarrheal, and antioxidant, reducing cardiovascular disease risk. While vinegar is generally used for antibacterial, antioxidant, antidiabetic, antitumor, antihypertensive, and many more benefits.